2014
DOI: 10.1080/09593330.2014.923516
|View full text |Cite
|
Sign up to set email alerts
|

Co-immobilization ofPseudomonas stutzeriYHA-13 andAlcaligenessp. ZGED-12 with polyvinyl alcohol–alginate for removal of nitrogen and phosphorus from synthetic wastewater

Abstract: Nitrogen (N) and phosphorus (P) are the two main factors causing water eutrophication. Immobilized micro-organisms have been widely studied in N and P removal. However, the effects of various immobilizing conditions on the removal efficiency of N and P using immobilized micro-organism beads (IMOBs) remain unclear. Polyvinyl alcohol (PVA) and alginate, as the two frequently immobilizing-used matrixes, were used for co-immobilizing Pseudomonas stutzeri YHA-13 and Alcaligenes sp. ZGED-12. PVA, alginate and CaCl₂c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…In addition, the predominant genus, Pseudomonas, increased to 56.13%, and Dechloromonas was present at a ratio of 5.19% after enrichment of the denitrifying bacterial community using nitrite as an electron acceptor. These bacteria were proved to be associated with the process of denitrifying phosphorus removal [45][46][47]. Previous studies reported that short-chain fatty acids (SCFAs) play an important role in biological phosphorus removal [48,49].…”
Section: Abundance and Function Of The Speciesmentioning
confidence: 99%
“…In addition, the predominant genus, Pseudomonas, increased to 56.13%, and Dechloromonas was present at a ratio of 5.19% after enrichment of the denitrifying bacterial community using nitrite as an electron acceptor. These bacteria were proved to be associated with the process of denitrifying phosphorus removal [45][46][47]. Previous studies reported that short-chain fatty acids (SCFAs) play an important role in biological phosphorus removal [48,49].…”
Section: Abundance and Function Of The Speciesmentioning
confidence: 99%
“…If the carbon source is insufficient, its nitrogen removal efficiency will decrease. To date, there have been many aerobic denitrifying bacteria isolated from the ecosystems, such as Pseudomonas stutzeri strain T1 [9], Vibrio diabolicus SF16 [10], Pseudomonas stutzeri YHA-13 [11], and Enterobacter cloacae strain HNR [12]. However, the literature describing the isolation of aerobic denitrifiers from constructed wetlands is quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus (P) is an abundant element in the lithosphere and is essential for all living organisms (Liu et al 2016). In aquatic systems, however, excessive P input can result in eutrophication, leading to harmful algal blooms that impact fish growth and animal and human health (Ascott et al 2016;Han et al 2014). P-induced eutrophication has been frequently reported and has attracted widespread concern.…”
Section: Introductionmentioning
confidence: 99%
“…P-induced eutrophication has been frequently reported and has attracted widespread concern. When the P concentration exceeds 0.1 mg L −1 and the total P (TP) content is much lower than that of total nitrogen (TN), indicating P limitation (i.e., TN:TP > 15:1), eutrophication occurs (Han et al 2014). In addition to eutrophicationtriggered deterioration of water quality, phosphate (PO 4 3− ) deposition is prevented by eutrophication, thereby reducing fertilizer production and global food security (Pantano et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation